Przyroda w perspektywie kulturoznawczej jako obszar badań - Kościelniak, Cezary (Humaniora. Czasopismo Internetowe, 2024)
Issues related to the environment, its protection, climate change, etc., has been increasingly entering the field of humanities and social sciences. The article examines the theoretical framework for building a research program for cultural studies for environment, a subfield of cultural sciences relating to issues of nature. The context of consideration oscillates around the development of economic-cultural, and cultural-political issues with themes related to nature and its protection. The text indicates that culturally operationalized knowledge of nature can have both research and implementation translations, becoming the basis for building strategies or theoretical foundations for reflection in the fields of conservation practices.